2012
DOI: 10.1016/j.biopsych.2012.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant Effects of Fibroblast Growth Factor-2 in Behavioral and Cellular Models of Depression

Abstract: Background Basic and clinical studies report that the expression of Fibroblast Growth Factor-2 (FGF2) is decreased in the Prefrontal Cortex (PFC) of depressed subjects or rodents exposed to stress, and increased following antidepressant treatment. Here, we aim to determine if: 1) FGF2/FGF receptor signaling is sufficient and required for mediating an antidepressant response behaviorally and cellularly; and 2) if the antidepressant actions of FGF2 are mediated specifically by the PFC. Methods The role of FGF2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
134
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 148 publications
(140 citation statements)
references
References 65 publications
5
134
0
1
Order By: Relevance
“…Given that antidepressant and anxiolytic medications induce growth factor expression (9-11), it may be that administering growth factors directly activates the same physiological mechanisms as classical anxiolytics and antidepressants. Indeed, work from others indicates FGF2 is necessary for the positive effect of antidepressants (8). However, one limitation of our FGF9 administration studies is the lack of anatomical specificity: that is, that administration into the lateral ventricle likely affects many brain regions in addition to the hippocampus.…”
Section: Fgf9 Expression Mediates Affect In An Animalmentioning
confidence: 94%
See 1 more Smart Citation
“…Given that antidepressant and anxiolytic medications induce growth factor expression (9-11), it may be that administering growth factors directly activates the same physiological mechanisms as classical anxiolytics and antidepressants. Indeed, work from others indicates FGF2 is necessary for the positive effect of antidepressants (8). However, one limitation of our FGF9 administration studies is the lack of anatomical specificity: that is, that administration into the lateral ventricle likely affects many brain regions in addition to the hippocampus.…”
Section: Fgf9 Expression Mediates Affect In An Animalmentioning
confidence: 94%
“…Rats exposed to chronic social defeat stress, an animal model recapitulating some aspects of MDD, showed decreased hippocampal FGF2 expression relative to unstressed controls (6), whereas subchronic and chronic administration of FGF2 had antidepressant properties (7,8). Moreover, administration of antidepressants and anxiolytics induced FGF2 expression (9-11), and recent studies suggested that this induction is necessary for the effectiveness of the antidepressants (8). Paralleling the human depression studies, hippocampal FGF2 was basally decreased in high-anxiety animals, but chronic administration in adulthood (12) or a one-time administration of FGF2 during early development (13) alleviated their anxious phenotype.…”
mentioning
confidence: 99%
“…Also selective infusion of FGF-2 in the PFC, but not into dorsal striatum, shows antidepressant-like and anxiolytic-like effects following forced swim test and novelty suppressed feeding test (46). Moreover, knockdown of FGF2 using single microinjection in the hippocampus resulted in an anxiety-like effect in outbred animals (26).…”
Section: Role Of Fgf2 In Altering the Levels Of Repressive H3k9me3 Anmentioning
confidence: 99%
“…CUS procedure. The CUS animals were subjected to exactly the same sequence of 12 stressors (2 per day for 35 d) described previously (32). FST.…”
Section: Methodsmentioning
confidence: 99%